Amygdala activation and symptom dimensions in obsessive–compulsive disorder. (January 2014) - Via, Esther; Cardoner, Narcís; Pujol, Jesús; Alonso, Pino; López-Solà, Marina; Real, Eva; Contreras-Rodríguez, Oren; Deus, Joan; Segalàs, Cinto; Menchón, José M.; Soriano-Mas, Carles; Harrison, Ben J.
Abstract : Background: Despite knowledge of amygdala involvement in fear and anxiety, its contribution to the pathophysiology of obsessive–compulsive disorder (OCD) remains controversial. In the context of neuroimaging studies, it seems likely that the heterogeneity of the disorder might have contributed to a lack of consistent findings. Aims: To assess the influence of OCD symptom dimensions on amygdala responses to a well-validated emotional face-matching paradigm. Method: Cross-sectional functional magnetic resonance imaging (fMRI) study of 67 patients with OCD and 67 age-, gender- and education-level matched healthy controls. Results: The severity of aggression/checking and sexual/religious symptom dimensions were significantly associated with heightened amygdala activation in those with OCD when responding to fearful faces, whereas no such correlations were seen for other symptom dimensions. Conclusions: Amygdala functional alterations in OCD appear to be specifically modulated by symptom dimensions whose origins may be more closely linked to putative amygdala-centric processes, such as abnormal fear processing.